Enhancing vulnerable communities’ resilience in public health through intersectoral collaboration: A study case of global empowerment steps’ project in Piyungan landfill - Yanuaristi, Herdifitrianne Saintissa; Hidayat, Ikhtiar Anugrah; Putri, Kintansari Adhyna (BKM Public Health and Community Medicine, 2021)
Objective: This study explores the role of social community to alleviate public health problems through partner collaboration, by three-sector interventions: economy, environment, and health. Content: Covid-19 pandemic has become a global challenge in public health efforts, mainly due to the barrier for social movements to take place and the shifting focus of government policy in public health intervention. This challenge becomes more tangible in vulnerable communities, namely but not limited to the economically disadvantaged communities. As their health heavily intersects with social factors, including housing environment, poverty, and inadequate information & education, their resilience in facing this pandemic highly depends on it. One example of these vulnerable communities is Piyungan Landfill Yogyakarta as the target population of this study. This study analyses the role of Global Empowerment Steps (GPS), a student-powered organization in the effort of increasing public health resilience by the utilization of multisectoral collaboration of its members and other stakeholders to alleviate public health problems in the area. GPS works with ten other organizations mostly student-powered, with each specific area of concern and conducting numerous projects that encourage society to engage and be responsible for their own health, as well as involving stakeholders responsible for social determinants of health in the area. By far, GPS has conducted serial entrepreneurial classes and empower local women to producing & marketing organic fertilizer to increase the community’s economic resilience, conducted researches and recommendations that has been presented to local government that resulted in technological improvement to separate the landfill from the residence for a better environmental resilience for the inhabitants, and increased health education of the inhabitants through numerous health education projects. In conclusion, the social community plays a significant role in increasing the resilience of vulnerable communities to face the pandemic. Keyword: Intersectoral collaboration; Public health resilience; Vulnerable community